Etching Time on Structural and Electrical Properties of Porous Silicon SERS Substrates for Non-Invasive Dengue-NS1 Detection - Ismai, N. F.; Ismail, L. N.; Y. Lee, Khuan; Zulhanip, A. Z.; Mohamad Hadis, N. S.; Mohd Radzol, A. R. (International Journal of Integrated Engineering, 2021)
Surface Enhanced Raman Spectroscopy (SERS) is a sensitive and specific analytical technique which has been explored in many applications, including disease detection. However, SERS performance is highly dependent on type of SERS substrate. This work is aimed to develop a SERS substrate that is sensitive to an early dengue virus biomarker known as Dengue virus nonstructural 1 (DENV-NS1) protein from saliva of infected patients. The new SERS substrate will allow non-invasive and rapid detection method for Dengue as early as day one of infection. Early detection of infection within the first five days is crucial to monitoring patients to help in reducing the fatality rate. Here, the electrochemical etching technique is employed to fabricate porous silicon (pSi) with variation in structural features to serve as the SERS substrate base. Variation in surface structural and electrical properties of pSi with etching time is recorded. Structural surface properties of the samples are investigated using the Field Emission Scanning Electron Microscope (FESEM) and energy-dispersive X-ray spectroscopy (EDX). While, the electrical properties are observed through I-V, resistivity and conductivity curve. From FESEM images, micro size cross-shaped porous structures are observed to have formed. Top-view reveals micro-size cross-shaped structures, while triangle-shaped structures from the cross-sectional view. The size of the structure formed increases with the etching time. Based on the structural and electrical properties an etching time between 20 to 28 minutes is found optimal for producing more uniform surface structures